Combination of aloe emodin, emodin, and rhein from Aloe with EDTA sensitizes the resistant Acinetobacter baumannii to polymyxins - Zhao, Yue; Zhang, Tingting; Liang, Yinping; Xie, Xiaoqing; Pan, Hongwei; Cao, Meng; Wang, Shuhua; Wu, Dalei; Wang, Jing; Wang, Chuandong; Hu, Wei (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundThe continuous emergence and spread of polymyxin-resistant Acinetobacter baumannii pose a significant global health challenge, necessitating the development of novel therapeutic strategies. Aloe, with its long-standing history of medicinal use, has recently been the subject of substantial research for its efficacy against pathogenic infections.MethodsThis study investigates the potential application of anthraquinone components in aloe against polymyxin-resistant A. baumannii by liquid chromatography-mass spectrometry, in vitro activity assessment, and construction of animal infection models.ResultsThe findings demonstrate that aloe emodin, emodin, rhein, and their mixtures in equal mass ratios (EAR) exhibit strain-specific antibacterial activities against polymyxin-resistant A. baumannii. Co-administration of EAR with EDTA synergistically and universally enhanced the antibacterial activity and bactericidal efficacy of polymyxins against polymyxin-resistant A. baumannii, while also reducing the frequency of polymyxin-resistant mutations in polymyxinssensitive A. baumannii. Following toxicity assessment on human hepatic and renal cell lines, the combination therapy was applied to skin wounds in mice infected with polymyxin-resistant A. baumannii. Compared to monotherapy, the combination therapy significantly accelerated wound healing and reduced bacterial burden.ConclusionsThe combination of EAR and EDTA with polymyxins offers a novel therapeutic approach for managing skin infections caused by polymyxinresistant A. baumannii.